Virome analysis of three Ixodidae ticks species from Colombia: A potential strategy for discovering and surveying tick-borne viruses (2021)
Ticks are a group of obligate blood-sucking ectoparasites that play a critical role in transmitting several important zoonotic pathogens that can infect animals and humans. Viruses are part of the tick microbiome and are involved in the transmission of important diseases. Furthermore, the little information on these as etiological agents of zoonoses suggests the need to study these microorganisms. For this reason, in this study, we sought to characterize the virome in Rhipicephalus microplus, Dermacentor nitens, and Rhipicephalus sanguineus s.l., which were collected from different domestic animals in Antioquia, Colombia. RNA sequencing was used for virome characterization in these three tick species, using RNA-dependent polymerase as a marker gene. Forty-eight sequences corresponding to 14 different viruses were identified, some of which were previously identified in the tick’s virome. Overall, these data indicate that ticks from domestic animals in cattle farms harbor a wide viral diversity at the local scale. Thus, the metatranscriptomic approach provides important baseline information for monitoring the tick virome and to develop future studies on their biology, host-virus interactions, host range, worldwide distribution, and finally, their potential role as emerging vector-borne agents